Cardiac ischemic symptoms among diabetic patients with their exercise tolerance test findings at a tertiary care hospital of Bangladesh (BIRDEM Medical Journal, 2023)
Background: Cardiovascular disease is the leading cause of death among diabetic patients. Diabetics who experience chest pain should get a full cardiac evaluation. Exercise tolerance test (ETT) is a noninvasive, less costly and relatively accurate test for evaluation of ischemic heart diseases. This study aimed to describe cardiac ischemic symptoms among diabetic patients and their ETT findings.Methods: This cross-sectional study was carried out among 82 diabetic patients with ischemic symptoms, in the Department of Cardiology, BIRDEM General Hospital, Dhaka from July to December 2018.Results: The mean±SD age was 60.91±11.68 years with male predominance (67%). The respondents had diabetes for an average of 8.34±4.92 years. Two-thirds of research participants were on insulin. The majority of the resting ECG results were ST-T changes (86.58%); mostly in anterior leads (54.9%) and ‘T’ inversion was predominant feature (64.2%) among all ST-T changes. The ETT result was positive in 69.72% of the individuals. During the ETT test, 57.31% of the individuals reached their goal heart rate. Test was terminated owing to tiredness in the majority of the individuals (86.58%). Chest pain and shortness of breath were significantly higher (p 0.042 and 0.011 respectively) in ETT positive participants. Aside from diabetes, the ETT positive participants had risk factors such as dyslipidaemia, hypertension, a family history of IHD and smoking (18.3%, 8.53%, 14.63% and 13.42% respectively).Conclusion: Over two-thirds of the diabetic patients with suspected IHD had positive ETT findings in this study.BIRDEM Med J 2023; 13(2): 67-75